Multiple disparities in adult mortality in relation to social and health care perspective: results from different data sources - Chhabi Lal Ranabhat; Chun-Bae Kim; Myung-Bae Park; Sambhu Acharaya (BMC, 2017)
Abstract Background Disparity in adult mortality (AM) with reference to social dynamics and health care has not been sufficiently examined. This study aimed to identify the gap in the understanding of AM in relation to religion, political stability, economic level, and universal health coverage (UHC). Methods A cross-national study was performed with different sources of data, using the administrative record linkage theory. Data was created from the 2013 World Bank data catalogue by region, The Economist (Political instability index 2013), Stuckler David et al. (Universal health coverage, 2010), and religious categories of all UN country members. Descriptive statistics, a t-test, an ANOVA followed by a post hoc test, and a linear regression were used where applicable. Result The average AM rate for males and females was 0.20 ± 0.10 and 0.14 ± 0.10, respectively. There was high disparity of AM between countries with and without UHC and between groups with low and high income. UHC and political stability would significantly reduce AMR by >0.41 in both sexes and high economic status would reduce male AMR by 0.44, and female AMR by 0.70. Conclusions It can be concluded that effective health care; UHC and political stability significantly reduce AM.